2013
DOI: 10.1128/mcb.01392-12
|View full text |Cite
|
Sign up to set email alerts
|

The Preference for Error-Free or Error-Prone Postreplication Repair in Saccharomyces cerevisiae Exposed to Low-Dose Methyl Methanesulfonate Is Cell Cycle Dependent

Abstract: bCells employ error-free or error-prone postreplication repair (PRR) processes to tolerate DNA damage. Here, we present a genome-wide screen for sensitivity to 0.001% methyl methanesulfonate (MMS). This relatively low dose is of particular interest because wild-type cells exhibit no discernible phenotypes in response to treatment, yet PRR mutants are unique among repair mutants in their exquisite sensitivity to 0.001% MMS; thus, low-dose MMS treatment provides a distinctive opportunity to study postreplication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
52
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 57 publications
5
52
0
1
Order By: Relevance
“…Our use of MMS2 to define errorfree bypass revealed clear functional redundancy between the two RAD18-regulated subpathways; neither an mms2D nor rev3D single mutant was sensitive to CLUV, but the double mutant was exquisitely sensitive. Similar synergism with respect to CLMMS has been previously reported (Huang et al 2013) and was confirmed here. RAD18-mediated error-free and error-prone pathways were interchangeable in terms of promoting growth, but epistasis analysis provided no information about the hierarchies or relative importance of these subpathways.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our use of MMS2 to define errorfree bypass revealed clear functional redundancy between the two RAD18-regulated subpathways; neither an mms2D nor rev3D single mutant was sensitive to CLUV, but the double mutant was exquisitely sensitive. Similar synergism with respect to CLMMS has been previously reported (Huang et al 2013) and was confirmed here. RAD18-mediated error-free and error-prone pathways were interchangeable in terms of promoting growth, but epistasis analysis provided no information about the hierarchies or relative importance of these subpathways.…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, whether DDT normally occurs directly at a stalled replication fork or as a gapfilling process after fork passage, and which mechanism of DDT normally predominates, have been controversial. Though it is possible to limit expression of Rad18 to specific points in the cell cycle and thereby uncouple DDT from replication (Daigaku et al 2010;Karras and Jentsch 2010), recent analyses suggest that template switching and TLS primarily occur during S and G2, respectively (Huang et al 2013). The strong mutator phenotype observed when error-free DDT is eliminated suggests that TLS is normally the minor bypass/tolerance pathway (Broomfield et al 1998;Minesinger and Jinks-Robertson 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All of these phosphorylation site mutants exhibited MMS sensitivity, indicating an important role in protecting cells from DNA damage. In particular, we identified MMS-induced phosphorylation sites on Xrs2 that are required for MMS resistance in the absence of the MRX activator, Sae2, and that affect telomere maintenance.KEYWORDS mass spectrometry; phosphorylation; methyl methanesulfonate; DNA damage checkpoint; genetic interaction; homologous recombination; telomere; DNA damage response C ELLS utilize excision repair and DNA damage tolerance pathways without significant delay of the cell cycle to address low levels of DNA base damage (Hishida et al 2009;Huang et al 2013), while more extensive damage is hallmarked by the activation of additional checkpoints, prolonged cell cycle arrest, and utilization of additional repair mechanisms (Lazzaro et al 2009). A classic example of an agent that elicits a profoundly different DNA damage response (DDR) at high and low doses is the monofunctional alkylating agent methyl methanesulfonate (MMS) (Friedberg and Friedberg 2006;Hanawalt 2015).…”
mentioning
confidence: 99%
“…C ELLS utilize excision repair and DNA damage tolerance pathways without significant delay of the cell cycle to address low levels of DNA base damage (Hishida et al 2009;Huang et al 2013), while more extensive damage is hallmarked by the activation of additional checkpoints, prolonged cell cycle arrest, and utilization of additional repair mechanisms (Lazzaro et al 2009). A classic example of an agent that elicits a profoundly different DNA damage response (DDR) at high and low doses is the monofunctional alkylating agent methyl methanesulfonate (MMS) (Friedberg and Friedberg 2006;Hanawalt 2015).…”
mentioning
confidence: 99%